Low‐grade ovarian serous carcinoma metastasis to the maxilla. (29th May 2018) - Tocaciu, S.; Fiddler, C.; Krzys, N.; Long, E.; Chambers, I.
Abstract: The maxillofacial region is an uncommon site for metastases from distant primary tumours, representing only 1–2% of malignancies at this site. Such metastases usually present in the mandible rather than the maxilla. The most common sites of primary tumour are the breast, lung and kidney. We describe the clinical, radiological and histologic features of the first‐known case of a low‐grade serous carcinoma of the ovary metastasising to the posterior maxilla. Low‐grade serous carcinoma of the ovary is an uncommon entity and is biologically distinct from high‐grade serous carcinoma. Extra‐abdominal spread is uncommon and bony metastases are rare. Intraosseous metastases are often associated with disseminated disease and confer a poor prognosis.